Confluent and reticulated papillomatosis associated with PFAPA syndrome. - Ahmed, O.; Mehmood, H.; Torchia, D. (European Journal of Pediatric Dermatology, 2025)
Confluent and Reticulated Papillomatosis (CRP), also known as Gougerot-Carteaud syndrome, is a very rare dermatosis with an as-yet unclear etiopathogenesis. It is characterized by asymptomatic, hyperpigmented papules and plaques, most commonly affecting the upper trunk, axillae, and neck. We present a clinical case in a 14-year-old girl, in whom the cutaneous manifestations of CRP are associated with Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Adenitis (PFAPA) syndrome.